(untitled) (Modern information system and technologies, 2018)
The article analyzes prospective microelectronic means of automation of technological processes of unloading and loading of agricultural units, selects a modern element base for the system being designed, considers the structural and principal schemes of a microprocessor system of program control using a programmable microprocessor controller. Keywords: agro-industrial complex, integral microcircuit, microprocessor, control device, software logic controller.